(untitled) (Ictus, 2025)
Clinical Image on ’Pseudoephedrine and the Risk of Posterior Reversible Encephalopathy Syndrome (PRES): Case Report in an Adult Patient’ presented in volume 5, Issue 1 of Ictus.